Freak Scenes American Indie Cinema and Indie Music Cultures - Sexton, Jamie (Music and the Moving Image : MMI, 2022)
The first academic book to explore indie music and indie music cultures on screenCombines historical, cultural, aesthetic and industry analysis to explore the functions and broader appeal of indie music on filmIncludes analyses of indie punk scenes on filmExamines gender and racial issues within indie music and filmFreak Scenes explores the increased licensing of indie music and representation of indie music cultures within American independent cinema since the 1980s. Indie music has, since the 2000s, become highlighted in some indie films as an attraction, but this book probes how the appeal of indie music stretches back to the late 1970s, when punk music made its impact on filmmaking.Sexton looks at a range of issues where indie music and indie film intersect, including commercial concerns, the growth of niche marketing, the increased employment of popular music in cinema and questions of authenticity, as well as the fraught tensions between commercial and artistic concerns. Case studies include: sonic authorship and indie music, representations of punk and indie scenes on screen, and an exploration of how racial and gender issues inform the representation and reception of indie cultures on film